Geological mapping in Kpf Blau Plantation and identify sea water intrusion of coastal aquifer Tumpat Area Using Electrical Resistivity Imaging and Geochemistry - Muhammad Khairul Hakim Helmi (2020)
Lojing Highland is located in SouthWest of Gua Musang part and mainly composed by high land use of agricultural activity while Tumpat is to be known as city near to the shore line and famous of coastal product. The present research focus on geological mapping and seawater intrusion into groundwater in parts of Lojing, Gua Musang and Tumpat respectively. Geological map produced is 1:25000 scale by traversing, field observation and petrographic study. Lithology mainly composed by mudstone, quartzite, limestone and schist unit in the study area. For seawater intrusion study, integrated approach is applied using ERI and chemical laboratory test using AAS and titration method. Total five survey line is done by using pole dipole and wenner configuration. The data collected of 200 meter using ABEM Terrameter LS, 42 electrode with spacing 5 meter and process using RES2DINV. Based on profile, all five location of survey line showing seawater intrusion. In addition, in situ analysis of physical parameter (TDS, TSS, Turbidity and etc) is done in selected well location and also chemical parameter is examined to analyze (Cl, Mn, Fe and etc). From the in situ chemical result, location 1 shows high salinity value as the location has shortest distance to the shore line. Based on ERI and chemistry result indicated the most intrusion shows in the depth of 30 meter below.